Why the University of Chicago's Museum Changed Its Name. (Biblical Archaeology Review)
The article reports on the renaming of the Oriental Institute Museum to the Institute for the Study of Ancient Cultures (ISAC) Museum, explaining the necessity of the name change due to evolving language and cultural sensitivities. It highlights the museum's rich collections, emphasizing its archaeological provenance and accompanying archives and mentions changes in programming and terminology, including a shift from BC/AD to BCE/CE and updates to display labels.